Analisis Rata-Rata Jam Tidur Mahasiswa Menggunakan One-Sample t-Test - Muhamad Bintang Abrar; Muhamad Fikri Maulana; Irgi Ahmad Maulana; Syahrial Frizky; Perani Rosyani (CV. Shofanah Media Berkah, 2025)
Sleep is a vital biological process that plays an essential role in maintaining physical health, mental stability, and emotional balance. Insufficient sleep duration can negatively affect concentration, memory, emotional regulation, and both academic and work productivity. Health organizations recommend a minimum of 7 hours of sleep per night for adults. However, many individuals, particularly students, fail to meet this recommendation due to academic demands, social activities, and excessive use of digital devices. This study aims to analyze whether the average sleep duration of respondents is less than 7 hours per night. The research method employed is a one-sample t-test with a comparison value of 7 hours. Data were collected through a questionnaire on respondents' average daily sleep duration. The analysis utilized descriptive and inferential statistics. Histogram visualization indicates that the distribution of sleep duration is predominantly below 7 hours. Furthermore, the one-sample t-test results show a p-value < 0.05, leading to the rejection of the null hypothesis. Therefore, it can be concluded that the average sleep duration of respondents is significantly lower than 7 hours. This study is expected to contribute academically to statistical applications and raise awareness of healthy sleep management.